Vratar' . The Goalkeeper - Timoshenko, Semyon (Lenfilm, 1936)
Duration: 01:12:00 Based on a short novel by Lev Kassil this comedy follows Anton Kandidov, a young stevedore from the Volga region and a born goalkeeper. Having moved to Moscow, Kandidov earns his fame as a member of the Gidroair football team and enhances rivalry between Girdoair and Torpedo, two Soviet football teams. Under the weight of his fame he quarells with the old friends, but having realized his mistakes, the 'prodigal friend' returns back to his team and his love. He heroically performs during the match of the Soviet players with the generic 'foreign' team Black Bulls.